Active Learning The Equilibrium between Student Writing and Critical Thinking - Millard, Thomas L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Graduate students at Montclair State College (New Jersey) were given the option of writing a journal article for publication in lieu of composing a standard term paper. The students were instructed to write essays, not research-focused papers, since the requirements for the latter were too time-consuming and perhaps beyond students' level of experience. They were allowed to submit their articles to the journal of their choice, as long as they observed the journal's editorial requirements; protocol for submitting manuscripts was discussed in class. A professional writer spoke to the students about the review process and prepared them for the possibility of rejection by sharing with them his own experiences with failure. At the same time, the class was reminded that a rejection was not to be considered a failure, since editors often provided some instructive comments or reasons for the rejection. Further, students were also assured that the articles would be graded on the same basis as traditional term papers had been. In spite of initial student resistance, the article option proved extremely successful; student papers have been published in local, regional, and national publications, and, more importantly, students' confidence in their writing ability has soared. (AEW)
ERIC Note: Paper presented at the Regional Conference on University Teaching (2nd, Las Cruces, NM, January 9-10, 1986). For the Proceedings of the conference, see ED 276 328.
Microfiche.
Keywords: Experiential Learning; Higher Education; Instructional Innovation; Research Papers (Students); Scholarly Journals; Teaching Methods; Writing (Composition); Writing Exercises; Writing for Publication; Writing Improvement; Writing Instruction; New Jersey; Journal Articles; Speeches/Meeting Papers; Reports, Descriptive